Synthesis of Carbon-Encapsulated Magnetic Iron Oxide Nanocomposites for Bioapplication - Wubshet Mekonnen Girma (International Journal of Biomaterials)
Carbon-encapsulated Fe3O4 nanoparticles (NPs) were successfully synthesized from a single precursor using one-step solvothermal methods. X-ray diffraction and transmission electron microscopy were used to characterize the as-prepared NPs, and UV-visible absorbance spectroscopy was used to check their optical properties. The morphological results revealed that Fe3O4@C, quasi-spherical Fe3O4 particles encapsulated by carbon. In addition, the carbon-encapsulated Fe3O4 NPs were conjugated with folic acid (FA) to be used as biomarkers in the diagnosis and treatment of tumour cells. Fourier transform infrared spectroscopy and UV-visible spectroscopic techniques were used to confirm the conjugation process.